(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
The most common anionic surfactants in the formulation of detergents are Linear Alkylbenzene Sulfonates (LAS), with an anionic sulfonate head group and a hydrophobic alkylbenzene tail group. The two primary synthetic detergents, together with sodium laureth sulphate, have been around for quite some time and may be found in many personal-care items such as shampoos, soaps, toothpaste, and laundry detergent. LAS is a relatively recalcitrant compound and not easily biodegraded. It is a major source of environmental contamination. Bioremediation can potentially give a significantly higher removal efficiency than standard physicochemical techniques. This review aims to compile information on the toxicity, biodegradation and assimilatory pathway of this class of compound. One of the challenges in the bioremediation of this class of compound is that there have been limited SDBS-degrading bacteria isolated and characterized to date and further work in the field of bioremediation should focus on the isolation of more degraders and carrying out further trials with micro-and mesocosms.